1977
DOI: 10.1080/00071667708416329
|View full text |Cite
|
Sign up to set email alerts
|

Stability of abdominal fat and meat of broilers: Relative effects of vitamin E, butylated hydroxytoluene and ethoxyquin1

Abstract: 1. α-Tocopheryl acetate (ATA) and ethoxyquin (EQ) markedly improved the stability of fat and meat of broilers fed on diets not supplemented with fat, while butylated hydroxytoluene (BHT) improved fat stability only.2. The stability of carcass fat of broilers fed on diets supplemented with acidulated soyabean-oil soapstock was improved by all three antioxidants, but BHT and EQ were more effective than ATA. Meat stability was improved only by EQ.3. The relationship between dietary EQ concentrations and the stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 14 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…The same is true with regard to the effect of the combination of EQ and ATA on meat stability (Tables 1 and 2). It is of interest to note that BHT alone did not affect meat stability of birds fed a fat-unsupplemented diet (Table 1; Bartov and Bornstein, 1977b), but in combination with ATA it markedly enhanced the protective effect of ATA (Table 1). Webb et al (1972) observed a similar phenomenon using a different type of diet.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The same is true with regard to the effect of the combination of EQ and ATA on meat stability (Tables 1 and 2). It is of interest to note that BHT alone did not affect meat stability of birds fed a fat-unsupplemented diet (Table 1; Bartov and Bornstein, 1977b), but in combination with ATA it markedly enhanced the protective effect of ATA (Table 1). Webb et al (1972) observed a similar phenomenon using a different type of diet.…”
Section: Discussionmentioning
confidence: 96%
“…However, the stability of the meat from these birds is improved only by EQ, and then only when used at levels higher than permitted for commercial diets. In contrast to EQ, BHT does not improve the stability of meat from broilers fed diets without fat supplement (Bartov and Bornstein, 1977b). A corresponding difference between the effects of EQ and BHT on meat stability was pointed out before by Webb et al (1972).…”
Section: Introductionmentioning
confidence: 92%
“…Even in the middle range, birds do not adapt their feed intake exactly and Fisher & Wilson (1974) found that at a constant nutrient:energy value, a I MJhg increase in the diet caused the fat content of the carcass to increase by 6.7 ghg. Bartov et al (1974b), Bartov & Bornstein (1977), Bartov (1979) and Fuller & Rendon (1977) reported that increases in the fat content of the diet, without alteration of the dietary E:P value, had no effect on the growth or carcass composition of broilers. However, Edwards et al (1973) and Fuller & Rendon (1977) found that the level and type of fat given (i.e.…”
Section: Nutrient Densitymentioning
confidence: 99%
“…A narrow E:P value such as would be obtained by increasing the dietary protein level, results in a less saturated carcass. The degree of saturation of carcass fat is of practical importance since unsaturated fatty acids are readily oxidized (Bartov & Bornstein, 1977). This gives rise to problems with rancidity of the fat, thus reducing the storage quality of the carcass, although the stability of the fat can be improved by supplementation of the diet with vitamin E (Bartov & Bornstein, 1977).…”
Section: Vol 45mentioning
confidence: 99%
“…Edwards and Hart (1971) observed no changes in carcass fat content of chicks when all of the nonprotein energy was derived from various dietary oils. Bartov et al (1974), Bartov and Bornstein (1977), Bartov (1977), Fuller and Rendon (1977), and Griffiths et al (1977b) reported that increase in the energy content of the diet through the addition of fat without altering the C:P ratio had no effect on carcass fat content of broilers. Griffiths et al (1977b) reported that the presence of added fat (0 to 9%) in diets formulated to be isocaloric with equivalent levels of lysine and methionine had no significant influence on abdominal fat pad weight of broilers at eight weeks of age.…”
Section: Introductionmentioning
confidence: 96%